PENGARUH MEDIA CERITA BERGAMBAR TERHADAP KEMAMPUAN MEMBACA NYARING PADA PELAJARAN BAHASA INDONESIA KELAS II DI MIT AL-FUAD KOTA TANGERANG - Suriadi, Rizka Surya Putri; Nur Latifah; Septy Nurfadhillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the effect of using picture story media on the ability to read aloud to class II students at MIT Al-Fuad, Tangerang City. The research approach used is quantitative, Quasi Experimental, Nonequivalent Control Group Design. The instrument used was a performance test of the ability to read aloud. Data analysis used the SPSS Version 22 application. The results of the posttest class hypothesis test calculation showed a Sig. (2-tailed) 0.015 < 0.05 then H0 is rejected and H1 is accepted. So it can be concluded that the use of picture story media influences the ability to read aloud to class II students at MIT Al-Fuad, Tangerang City. Keywords: Picture Story Media, Reading Aloud.